Opposite Effects of Neuroprotective Cannabinoids, Palmitoylethanolamide, and 2-Arachidonoylglycerol on Function and Morphology of Microglia - Hohmann, Urszula; Pelzer, Markus; Kleine, Joshua; Hohmann, Tim; Ghadban, Chalid; Dehghani, Faramarz (Frontiers in Neuroscience, 2019)
Various studies performed in cultured cells and in in vivo models of neuronal damage showed that cannabinoids exert a neuroprotective effect. The increase in cannabinoids and cannabinoid like substances after stroke has been postulated to limit the content of neuronal injury. As well accepted, inflammation and neuronal damage are coupled processes and microglial cells as the main intrinsic immunological effector within the brain play a central role in their regulation. Treatment with the endocannabinoid, 2-arachidonoylglycerol (2-AG) or the endocannabinoid-like substance, palmitoylethanolamide (PEA) affected microglial cells and led to a decrease in the number of damaged neurons after excitotoxical lesion in organotypic hippocampal slice cultures (OHSC). 2-AG activated abnormal cannabidiol (abn-CBD) receptor, PEA was shown to mediate neuroprotection via peroxisome proliferator-activated receptor (PPAR)α. Despite the known neuroprotective and anti-inflammatory properties, the potential synergistic effect, namely possible entourage effect after treatment with the combination of these two protective cannabinoids has not been examined yet. After excitotoxical lesion OHSC were treated with PEA, 2-AG or a combination of both and the number of damaged neurons was evaluated. To investigate the role of microglial cells in PEA and 2-AG mediated protection, primary microglial cell cultures were treated with lipopolysaccharide (LPS) and 2-AG, PEA or a combination of those. Thereafter, we measured NO production, ramification index, proliferation and PPARα distribution in microglial cells. While PEA or 2-AG alone were neuroprotective, their co-application vanished the protective effect. This behavior was independent of microglial cells. Furthermore, PEA and 2-AG had contrary effect on ramification index and on NO production. No significant changes were observed in the proliferation rate of microglial cells after treatment. The expression of PPARα was not changed upon stimulation with PEA or 2-AG, but the distribution was significantly altered. 2-AG and PEA mediated neuroprotection was abolished when co-applied. Both cannabinoids exert contrary effects on morphology and function of microglial cells. Co-application of both cannabinoids with different targets did not lead to a positive additive effect as expected, presumably due to the contrary polarization of microglial cells.